Profitability of Continuous Improvement Process in Developing Human Resource Plan for Construction Companies in Malaysia - Muhammed, Mai Abdulkadir; Kabiru, Shehu; Abdulkarim, Jimoh Abdullateef; Riazi, Salman Riazi Mehdi; Nawi, Mohd Nasrun Mohd (International Review of Management and Marketing, 2017)
The need for continuous improvement (CI) for the productivity of construction professionals and operatives in the Malaysian construction industry cannot be overemphasized. Companies today seek competitive edge in terms of profitability. For any organization or company to excel, it must consider its personnel as the most valuable resource. Nations and organizations must take the aspect of their human resources in a dynamic concept, otherwise they risk losing their competitiveness and being overtaken by their competitors. This paper is aimed at assessing the profitability of integrating a CI process in the human resource development plan of Malaysian construction companies. The main objectives set out includes, to determine the implementation strategies of CI in companies; identify the benefits of human resource development in Malaysian construction industry; examine critical success factors to promote CI in Malaysian construction industry; identify the barriers and challenges to CI in Malaysian construction companies. The method used is review paper by drawing inferences from the findings of selected journals. The findings revealed that CI in form of training and performance appraisal, are positively related to the competitiveness and profit of a company. Among the benefits of implementing CI are that employees working under healthy environment, customer’s satisfaction are guaranteed and increased company financial returns. CI can increase profitability, various diagrams and analysis are tools used in CI. The study established that Malaysian construction industry is rated low in the aspect of CI of its workforce. Keywords: Continuous Improvement Process, Profitability, Human Resources, Construction Industry, Companies JEL Classifications: M1, E24, L7, M11